Privacy in the Use of Artificial Intelligence Technologies in Banking Operations - Tahseen Mohammed Hasan Al-Khaleel, Dr. Akram (Basra studies journal, 2025)
The use of artificial intelligence (AI) technologies in banking operations is considered one of the most significant indicators of today’s rapid technological advancement, which has cast its shadow over the banking sector just as it has over other aspects of life. However, this use is not without certain risks that may affect either bank customers or the bank itself, as a result of relying on these technologies in their financial transactions. Therefore, an appropriate legislative framework is required to address these developments and the modern transformations that have taken place in the banking sector. Such legislation should identify the party responsible for compensating the damages arising from the use of AI technologies and clarify the legal basis for this liability—whether the harm is suffered by the bank’s clients or by the bank itself as a consequence of such use.